Fluctuations in grandiose and vulnerable narcissistic states: A momentary perspective - Edershile, Elizabeth A. (J Pers Soc Psychol, 2020)
Theories of narcissism emphasize the dynamic processes within and between grandiosity and vulnerability. Research seeking to address this has either not studied grandiosity and vulnerability together or has used dispositional measures to assess what are considered to be momentary states. Emerging models of narcissism suggest grandiosity and vulnerability can further be differentiated into a three-factor structure – Exhibitionistic Grandiosity, Entitlement, and Vulnerability. Research in other areas of maladaptive personality (e.g., borderline personality disorder) has made headway in engaging data collection and analytic methods that are specifically meant to examine such questions. The present study took an exploratory approach to studying fluctuations within and between grandiose and vulnerable states. Fluctuations – operationalized as gross variability, instability, and lagged effects – were examined across three samples (two undergraduate and a community sample oversampled for narcissistic features; Total person N = 862; Total observation N = 36,631). Results suggest variability in narcissistic states from moment to moment is moderately associated with dispositional assessments of narcissism. Specifically, individuals who are dispositionally grandiose express both grandiosity and vulnerability, and vary in their overall levels of grandiosity and vulnerability over time. On the other hand, dispositionally vulnerable individuals tend to have high levels of vulnerability and low levels of grandiosity. Entitlement plays a key role in the processes that underlie narcissism and narcissistic processes appear unique to the construct and not reflective of broader psychological processes (e.g., self-esteem). Future research should consider using similar methods and statistical techniques on different timescales to study dynamics within narcissism.